A model-based estimate of the groundwater budget and associated uncertainties in Bengaluru, India. Issue 1 (2nd January 2021) - Tomer, S. K.; Sekhar, M.; Balakrishnan, K.; Malghan, Deepak; Thiyaku, S.; Gautam, M.; Mehta, Vishal K.
ABSTRACT: Understanding the water metabolism of developing country cities is challenging because of insufficient knowledge of how social, infrastructural and hydrological dimensions are coupled. Using Bengaluru City in India, we demonstrate how fine-resolution data can inform model-based estimates of urban groundwater budgets. Groundwater levels were measured at 154 locations in 2016 and used to estimate model parameters and uncertainty. Total water use was estimated at 1470 million litres per day (MLD). Groundwater pumping meets the majority of this use (827 MLD), followed by utility water supply (643 MLD). Total recharge was estimated at 973 MLD. Natural recharge is a much smaller portion (183 MLD) compared to anthropogenic recharge from leaking water supply and wastewater systems (791 MLD). The city experienced a net negative groundwater balance (40 MLD). Natural recharge and total water use estimates showed lower uncertainty. Spatial variation in these fluxes is described and related to secondary information.